Cellular Localization of Enzymatically Active Thrombin in Intact Human Tissues by Hirudin Binding - Zacharski, Leo R; Memoli, Vincent A; Morain, William D; Schlaeppi, Jean-Marc; Rousseau, Sandra M (Thrombosis and Haemostasis, 1995)
Cellular sites of coagulation activation within complex, intact tissues have been studied by immunohistochemical techniques. Hirudin, a specific and high affinity inihibitor of the active site of thrombin, together with antibody to hirudin were applied to sections of AMeX-fixed specimens of normal lung, kidney, placenta, freshly incised skin and unperturbed skin obtained at fresh autopsy; to rheumatoid synovial tissue; and to malignant tissue from a variety of tumor types. Staining for thrombin was observed selectively on pulmonary alveolar, rheumatoid synovial, and placental macrophages that express an intact extrinsic coagulation pathway. Staining was also observed restricted to the endothelium of capillaries in freshly incised skin but not in either unperturbed skin or in aged incisions. Staining of tumor cell bodies was observed in small cell carcinoma of the lung, renal cell carcinoma, and malignant melanoma tissues that we found previously to show tumor cell-associated procoagulant activity. This staining occurred commonly on cells within the tumor mass that were distant from stromal fibrinogen/fibrin. By contrast, tumor-associated macrophage but not tumor cell staining was seen in adenocarcinoma and squamous cell carcinoma of the lung, and little or no staining was seen in colon cancer tissue. Negative controls in which either the hirudin probe or its antibody were omitted failed to show staining. These results are in accord with previous findings and suggest that such techniques may be useful for studying the cellular sites of thrombin generation in intact tissues. We postulate that administration of potent and specific thrombin antagonists, such as hirudin, to patients with relevant tumor types might be followed by homing of hirudin to tumor cells in vivo so that effects of local thrombin generation on malignant progression can be determined.